(untitled) (Jurnal Ilmiah Pertanian Nasional, 2023)
Jicama (Pachyrhizus erosus) is a plant that has been cultivated by farmers in Kediri Regency. Initially, farmers planted jicama in monoculture during one growing season. Furthermore, some farmers develop an intercropping pattern of jicama and choy sum to increase the chances of greater yields and help reduce expenses because maintenance of two crops can be done at one time. The research was conducted in Ngampel Village, Papar District, one of jicama producing centers in Kediri Regency, to investigate the income comparison and the feasibility of jicama farming using different cropping patterns. Data were taken from all the farmers in the research location who cultivated jicama as many as 60 farmers, who were divided into two categories of cropping pattern application. The data were then analyzed by cost-income, farming feasibility analysis, and two independent sample tests. The results showed that the average total cost of jicama farming intercropped with choy sum was IDR28,439,687 per ha with an average income of IDR48,625,350 per ha. Meanwhile, jicama monoculture farming required an average cost of IDR24,395,391 per ha and generated an average income of IDR35,302,661 per ha. The statistical test results also proved that the costs and income of farmers applying the penanaman sela pattern exceeded monocultures. Both cropping patterns were feasible and profitable with R/C ratios of 2.57 and 2.78 for monoculture and intercropping respectively. Â Bengkuang (Pachyrhizus erosus) merupakan tanaman yang mulai dibudidayakan oleh petani di Kabupaten Kediri. Awalnya petani menanam bengkuang secara penanaman tunggal pada suatu musim tanam. Selanjutnya, sebagian petani mengembangkan pola penanaman sela untuk meningkatkan peluang hasil yang lebih besar dan membantu menekan biaya pengeluaran karena perawatan dua jenis tanaman yang bisa dilakukan dalam satu waktu sekaligus. Penelitian dilakukan di sentra bengkuang Kediri, yang berlokasi di Desa Ngampel, Kecamatan Papar, untuk mengetahui perbandingan pendapatan dan kelayakan usahatani bengkuang dengan penerapan pola tanam berbeda. Data diambil dari semua petani di lokasi penelitian yang membudidayakan bengkuang sebanyak 60 petani, yang terbagi dua kategori penerapan pola tanam. Data kemudian dianalisis dengan analisis biaya dan pendapatan, analisis statistik uji beda rata-rata, dan analisis kelayakan usahatani. Rerata biaya total per hektar tanam sela bengkuang-sawi sebesar Rp28.439.687 dengan pendapatan per hektar Rp48.625.350. Sementara tanam tunggal bengkuang membutuhkan rerata biaya per hektar Rp24.395.391 untuk menghasilkan pendapatan per hektar Rp35.302.661. Hasil uji statistik beda rata-rata membuktikan bahwa biaya dan pendapatan petani bengkuang penerap pola tanam sela memang melebihi penanaman tunggal. Kedua pola tanam sangat layak diusahakan dan menguntungkan dengan nilai rasio R/C 2,57 dan 2,78 masing-masing untuk usahatani bengkuang penanaman tunggal dan penanaman sela dengan sawi.